2018
DOI: 10.1039/c7ta10995d
|View full text |Cite
|
Sign up to set email alerts
|

Photobleaching dynamics in small molecule vs. polymer organic photovoltaic blends with 1,7-bis-trifluoromethylfullerene

Abstract: C60(CF3)2 stabilizes OPV donors toward photodegradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
(32 reference statements)
0
16
0
Order By: Relevance
“…Indeed, recent literature results have shown that phase separation of the polymer and fullerene can happen with time; this phenomenon has been independently observed both with blends of C 60 (CF 3 ) 2 (ref. 28) and in systems with PCE11. 17 Finally, in some cases the uorinated fullerene acts as a more efficient stabilizer of the polymer towards photodegradation, and in other cases PC 60 BM is more efficient.…”
Section: Photobleachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent literature results have shown that phase separation of the polymer and fullerene can happen with time; this phenomenon has been independently observed both with blends of C 60 (CF 3 ) 2 (ref. 28) and in systems with PCE11. 17 Finally, in some cases the uorinated fullerene acts as a more efficient stabilizer of the polymer towards photodegradation, and in other cases PC 60 BM is more efficient.…”
Section: Photobleachingmentioning
confidence: 99%
“…27 Indeed, we recently observed that C 60 (CF 3 ) 2 could stabilize the initial rate of photobleaching in small molecule and polymer blends by a factor of 15 relative to PC 70 BM. 28 However, phaseseparation of C 60 (CF 3 ) 2 from the small molecule donor material was observed that resulted in dramatic acceleration of the photobleaching rate in less than 24 h of white light exposure. Those results suggest that if there is a substantial difference in miscibility between different fullerenes and a given donor material, the EA of the fullerene alone will not be the only factor determining its stabilizing effect.…”
Section: Introductionmentioning
confidence: 99%
“…Blending small molecules with polymers is an important approach to construct efficient optoelectronic devices based on heterojunctions. New charge transfer complexes [20][21][22] can be thus Crystals 2021, 11, 1022 2 of 8 produced and utilized to investigate new photophysics and to develop new photovoltaic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Crystals 2021, 11, x FOR PEER REVIEW 2 of 9 optoelectronic devices based on heterojunctions. New charge transfer complexes [20][21][22] can be thus produced and utilized to investigate new photophysics and to develop new photovoltaic devices. Figure 1 shows the basic principles for the formation of the EPPTC crystals inside a solid film of polymer chains.…”
Section: Introductionmentioning
confidence: 99%
“…The degradation mechanisms of polymer:fullerene‐based solar cells have been a focus of extensive study in the last decade and are now reasonably well understood. Under illumination, polymer solar cells typically show a strong initial decrease in device performance (“burn‐in”), caused by formation of defects in the bandgap . In addition, exposure to oxygen leads to p‐type doping in some polymer systems, which causes increased bimolecular recombination or formation of traps which in turn impede charge generation and transport .…”
Section: Introductionmentioning
confidence: 99%